PENERAPAN METODE EOQ DALAM PENGAMBILAN KEPUTUSAN PERSEDIAAN PADA PT. PCI ELEKTRONIK INTERNASIONAL BATAM - Aznedra A (Universitas Riau Kepulauan, 2016)
Decision making is a process of selecting the best alternative of several alternatives systematically to follow-up (use) as a way of solving the problem, then the decision-making supplies are needed within the company. that play a role in management decision making. In an enterprise, inventory is an important asset and must be managed well. To manage inventory, management must make decisions about the number of orders, when they are placed, and how much inventory should be kept with the cost of maintenance and storage of supplies to every decision the most minimal. In this study, the authors tried to assess whether the method used has been to support inventory management decision making by the company management, by performing calculations using the method of EOQ, ROP and SS. The results showed that the method applied by PT. International Electronics PCI Batam do not act to support decision-making supplies by the management company for not considering the costs of maintenance and storage of supplies in every decision taken, it is recommended that PT PCI Electronic international Batam applying the method of EOQ, ROP and SS in decision-making supplies.